FACTORS CONTRIBUTING TO THE DEVELOPMENT OF LOCOREGIONAL RECURRENCE (Global Conference on Medical and Health Sciences, 2026)
Locoregional recurrence remains one of the leading causes of disease progression following radical treatment for malignant neoplasms. Identification of risk factors associated with recurrence is essential for predicting patient outcomes, optimizing therapeutic strategies, and developing individualized follow-up programs.
Keywords: locoregional recurrence, risk factors, oncology, prognosis, adjuvant therapy.